Enlightenment of scientific knowledge at the kindergarten teachers and its relationship with some variables - حيدر مسير حمد دلال جاسم عبد الرضا (College of Education for Women, 2019)
A kindergarten teacher is one of the most important elements in the educational process, since she is totally relied upon in kindergartens. Therefore, she could have basic and healthy characteristics to improve the educational process by directing the child towards a perfect growing upEducating and raising up a child should be an organized process that makes desirable changes in the child's behavior in order to improve different sides of his personality, such as his appearance side, his mental side, and his social side. This research aims at: 1- Measuring the scientific brilliance in kindergarten teachers. 2- Investigating the statistical significant differences of the scientific brilliance among kindergarten teachers in accordance with the factors of educational status service, the type of kindergarten (public - private)